Purchase Procedure and Supplier Evaluation for Food Processing Firms in Gujarat - Maitrak R. Pandya; Dilip R. Vahoniya (Archives of Current Research International, 2025)
The food processing industry, both globally and in India, is undergoing rapid transformation driven by increasing consumer demand for safe, high-quality, and convenient products. As a major agricultural producer, India plays a pivotal role in the global food supply chain, particularly in the expanding frozen food segment, where demand for ready-to-eat and ready-to-cook products is rising steadily. This study focuses on the procurement and supplier evaluation practices of a leading frozen food manufacturer based in Gujarat. It critically examines the company’s structured procurement framework, which emphasizes transparency, cost optimization, and strict compliance with food safety and regulatory standards. The procurement process involves close coordination among cross-functional departments including production, quality control, and new product development (NPD), ensuring seamless sourcing and consistent product quality. Primary data were collected from 20 procurement professionals across the sector using a structured questionnaire. The Henry Garrett Ranking method was applied to prioritize supplier evaluation criteria based on practical significance. The analysis revealed that product quality was considered the most crucial factor in supplier selection with a Garrett mean score of 78.40, followed by price (75.00) and accuracy of delivery (70.36). Other notable criteria included rejection handling, supplier capability, and service responsiveness. The findings provide a practical and data-driven framework that food processing firms can adopt to enhance supplier selection, streamline procurement workflows, and strengthen supply chain resilience. The study also contributes to existing literature by bridging the gap between procurement theory and its real-world application in the Indian frozen food industry.